1)log5(6+7x)=log5(4+x)+1
log5(6+7x)/(4+x)=1
(6+7x)/(4+x)=5
![x\neq-4 x\neq-4](https://tex.z-dn.net/?f=x%5Cneq-4+)
6+7x=20+5x
2x=14
x=7
2) log2(4-x)=log2(1-3x)+1(
(4-x)/(1-3x)=2
![x\neq1/3 x\neq1/3](https://tex.z-dn.net/?f=x%5Cneq1%2F3)
4-x=2-6x
5x=-2
x=-2/5
3) log5(8+5x)=log5(4-3x)+1
(8+5x)/(4-3x)=5
![x\neq4/3 x\neq4/3](https://tex.z-dn.net/?f=x%5Cneq4%2F3)
8+5x=20-15x
20x=12
x=3/5
4)log2(4+5x)=log2(1-4x)+1
(4+5x)/(1-4x)=2
![x\neq1/4 x\neq1/4](https://tex.z-dn.net/?f=x%5Cneq1%2F4)
4+5x=2-8x
13x=-2
x=-2/13
5)log3(6+5x)=log3(3+5x)+1
(6+5x)/(3+5x)=1
![x\neq-3/5 x\neq-3/5](https://tex.z-dn.net/?f=x%5Cneq-3%2F5)
6+5x=9+15x
x=-3/10
6) log4(4+3x)=log4(1-5x)+1
(4+3x)/(1-5x)=4
![x\neq1/5 x\neq1/5](https://tex.z-dn.net/?f=x%5Cneq1%2F5)
4+3x=4-20x
x=0